2004
DOI: 10.1002/adsc.200404110
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Oxidations Mediated by Nitroxyl Radicals

Abstract: The use of nitroxyl radicals, alone or in combination with transition metals, as catalysts in oxidation processes is reviewed from both a synthetic and a mechanistic viewpoint. Two extremes of reactivity can be distinguished: stable (persistent) dialkylnitroxyls, such as the archetypal TEMPO, and reactive diacylnitroxyls, derived from N-hydroxy imides, such as N-hydroxyphthalimide (NHPI). The different types of reactivity observed are rationalized by considering the bond dissociation energies (BDEs) of the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
120
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 619 publications
(121 citation statements)
references
References 133 publications
(136 reference statements)
1
120
0
Order By: Relevance
“…[8] In previous works, it has been reported that N-hydroxyphthalimide (NHPI), in combination with transition metal acetates, can promote the oxidation of cycloalkanes and alkylbenzenes with oxygen under homogeneous conditions by using acetic acid as the solvent. [9][10][11] However, the selectivity for the oxidation of industrially relevant cyclohexane by using NHPI was low due to the formation of significant amounts of dicarboxylic acids. A heterogeneous version of this system has been reported by using silica or zeolites as NHPI supports, which avoids the need for corrosive acetic acid.…”
Section: Introductionmentioning
confidence: 97%
“…[8] In previous works, it has been reported that N-hydroxyphthalimide (NHPI), in combination with transition metal acetates, can promote the oxidation of cycloalkanes and alkylbenzenes with oxygen under homogeneous conditions by using acetic acid as the solvent. [9][10][11] However, the selectivity for the oxidation of industrially relevant cyclohexane by using NHPI was low due to the formation of significant amounts of dicarboxylic acids. A heterogeneous version of this system has been reported by using silica or zeolites as NHPI supports, which avoids the need for corrosive acetic acid.…”
Section: Introductionmentioning
confidence: 97%
“…17,18 In such processes, oxidation was achieved through the radical route and the active catalytic species of phthalimide N-oxyl radical (PINO) originated from NHPI under an oxygen atmosphere. 19,20 A catalyst system including NHPI and acetaldehyde showed promising catalytic performance in the oxidation of organic substrates in the absence of any metal.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the presence of a high number of oxygen vacancies could favor the activation of the NHPI to form the phthalimide N-oxyl radical (PINO), promoting the absorption of the hydrogen atom from the hydrocarbon to form an alkyl radical, which reacts with O 2 molecules to afford oxygenated compounds. [6][7][8][9][10][11] The hypostoichiometric perovskite was also very efficient in the aerobic oxidation of other alkyl aromatics (toluene or ethylbenzene; Table 2). In both cases, the conversion of alkyl aromatics was very high (> 99.5 %).…”
mentioning
confidence: 98%
“…This reaction was carried out using various catalytic systems-(La,Sr) 0.5 (Mn,Co) 0.5 O 3Àd /NHPI, (La,Sr) 0.5 (Mn,Co) 0.5 O 3 / NHPI-and, for comparative purposes to benchmark the present state of the art, we employed Co(OAc) 2 /Mn(OAc) 2 / NHPI, which is the best catalytic system described in literature for soft reaction conditions. [6][7][8] The p-xylene conversion was 100 % for all the systems (Table 1). However, the product distribution is highly affected by the catalyst used.…”
mentioning
confidence: 99%